Keteladanan Orang Tua dan Guru dalam Pertumbuhan dan Perkembangan Anak Usia Dini di TK PAUD Nurul Islam Payabenua - Dewi, Ratna (NOURA: Jurnal Kajian Gender dan Anak, 2019)
This study has a background that phenomena in the world of education must be addressed immediately, because there are still many as an educator who are not able to carry out their duties and there are still many educators who provide learning that is not competent in their fields of science, which has a negative impact on the next generation. The example of parents and teachers makes the concept of education the most superior in the process of growth and development of students. Formulation The problem of this research is how to understand the example of parents and teachers for educate children in their relevance to the growth and development of children Exemplary Parents and Teachers in the Growth and Development of Early Childhood TK Paud in Payabenua. This research is a qualitative descriptive study. The approach used in this study is a historical and philosophical approach. In that the concept of exemplary is the most influential method that ensures its success in preparing and forming children to form moral, social, and spiritual persons, with the best example in the child’s view, who will be imitated in their actions and horns, and manners, whether consciously or not , even printed in the soul and feelings of the child, about the picture of the educator, both in speech and deed. Therefore as an educator must have a good exemplary figure, according to the criteria of the teachings that have been given by Islam about akhlakul karimah.